The dynamic consequences of state-building: Evidence from the French Revolution - Cédric Chambru; Emeric Henry; Benjamin M. Marx (University of Zurich, Department of Economics, 2022)
How do radical reforms of the state shape economic development over time? In 1790, France's first Constituent Assembly overhauled the kingdom's organization to set up new administrative entities and local capitals. In a subset of departments, new capitals were chosen quasi-randomly as the Assembly abandoned its initial plan to rotate administrative functions across multiple cities. We study how exogenous changes in local administrative presence affect the state's coercive and productive capacity, as well as economic development in the ensuing decades. In the short run, proximity to the state increases taxation, conscription, and investments in law enforcement capacity. In the long run, the new capitals and their periphery obtain more public goods and experience faster economic development. One hundred years after the reform, capitals are 40% more populated than comparable cities in 1790. Our results shed new light on the intertemporal and redistributive impacts of state-building in the context of one of the most ambitious administrative reforms ever implemented.
Keywords: D70; H41; H71; O18; O43; 330; State capacity; state-building; administrative reform; economic development